Faktor-Faktor Yang Mempengaruhi Kemiskinan di Kabupaten Karangasem - Dwi Cahya, Ni Kadek Kartini; Nata, Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
Poverty is one of the social problems that have become a social problem that has become a global problem in almost all countries, including Indonesia. Poverty itself is also caused by a variety of factors that are not much different from the unemployed. The purpose of this study was to determine the factors that affect poverty in Karangasem regency. This research was conducted in Karangasem regency. Data collected through the documents contained in the BPS Bali. The data used in this research is secondary data is data time series that began in 1999 until 2014. The analysis technique used in this research is multiple linear regression. Based on the analysis result that the GDP and education have negative and significant effect of on poverty. Unemployment as well as have a positive effect on poverty in Karangasem regency.
Keywords: GDP, unemployment, education, poverty